Expediting Oxygen Evolution by Optimizing Cation and Anion Complexity in Electrocatalysts Based on Metal Phosphorous Trichalcogenides. Issue 9 (18th January 2023) - Li, Weiwei; Li, Cong; Dong, Hongliang; Zhang, Xiaoliang; Liu, Junxiu; Song, Meng; Wang, Gui; Zhao, Lei; Sheng, Hongwei; Chen, Bin; Zhang, Hengzhong
Abstract: Purposely changing the rate‐determining step (RDS) of oxygen evolution reaction (OER) remains a major challenge for enhancing the energy efficiency of electrochemical splitting of water. Here we show that the OER RDS can be regulated by simply varying the cation and anion complexity in a family of the metal phosphorous trichalcogenide electrocatalysts (MPT3, where M=Fe, Ni; T=S, Se), achieving an exceptionally high OER activity in (Ni, Fe)P(S, Se)3, as demonstrated by its ultra‐low Tafel slope (34 mV dec −1 ) and a very low overpotential compared to many relevant OER catalysts. This is strongly supported by density functional theory calculations, which showed that this catalyst has a nearly optimal OER activity descriptor value of Δ G (O*)−Δ G (OH*)=1.5 eV. We also found that the activity descriptor is proportional to a newly proposed cation/anion complexity index that consists of pairwise contributions from cation‐anion bonds in a catalyst compound, revealing the pivotal role of the cation‐anion interactions in determining the catalyst performance and providing a simple way for predicting catalytic activities. Abstract : The rate of the oxygen evolution reaction (OER) increases with the cation/anion complexity of the employed electrocatalysts based on metal phosphorous trichalcogenides. The most complex catalyst has a nearly optimum OER activity descriptor value and a different rate‐determining step with respect to its sibling catalysts, making it the most active catalyst in the family.